2010
DOI: 10.1097/rli.0b013e3181ea703d
|View full text |Cite
|
Sign up to set email alerts
|

Where Contrast Agent Concentration Really Matters – A Comparison of CT and MRI

Abstract: Contrast agent concentration is a key parameter for the optimization of dynamic imaging techniques such as angiography or perfusion in CT, whereas in dynamic MRI, contrast agent dose and relaxivities are the leading parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…20,37 Thus, 3 blinded readers found no relevant benefit for the more highly concentrated gadobutrol in terms of lesion conspicuity, visualization, or sensitivity for detection. Rather, our intraindividual comparison of gadobenate dimeglumine and gadobutrol at an identical dose of 0.1 mmol/kg of body weight confirms that significantly improved qualitative and quantitative enhancement of brain tumors is achieved with gadobenate dimeglumine without any difference in safety.…”
Section: Discussionmentioning
confidence: 98%
“…20,37 Thus, 3 blinded readers found no relevant benefit for the more highly concentrated gadobutrol in terms of lesion conspicuity, visualization, or sensitivity for detection. Rather, our intraindividual comparison of gadobenate dimeglumine and gadobutrol at an identical dose of 0.1 mmol/kg of body weight confirms that significantly improved qualitative and quantitative enhancement of brain tumors is achieved with gadobenate dimeglumine without any difference in safety.…”
Section: Discussionmentioning
confidence: 98%
“…This observation is in accordance with the findings of Thilmann et al, who also found identical contrast bolus shapes measured as FWHM after fast injection of 0.1 and 0.2 mmol/kg bw of the 1.0 M agent gadobutrol and 0.1 mmol/kg bw of the 0.5 M agent gadobenate. If very short (<5 sec) contrast agent injection times are used, a lower contrast volume with additional reduction of the injection time does not result in a more compact bolus shape in the arterial vessels or tissues because the final bolus shape in the ROI is determined by physiologic bolus‐widening effects occurring during the passage of the bolus through the body . For conventional brain tumor imaging the r1 relaxivity of the GBCA is the most important factor for contrast enhancement on T 1 ‐weighted images.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is not unexpected, given that image acquisition for morphologic imaging of brain tumors typically begins at least 3-5 minutes following contrast administration, by which time contrast equilibration will have occurred, which would obviate any potential benefits of a higher administered concentration. 12,13 Second, although r1 relaxivity is a major factor for contrast efficacy, 13 the slightly different r1 relaxivity values for gadobutrol and gadoteridol are insufficient to show any discernable clinical effect, either for qualitative or quantitative lesion enhancement or for diagnostic performance.…”
Section: Discussionmentioning
confidence: 99%